The use of ATR-FTIR to track the degradation of single-use polystyrene cup lids during 24 months of temperate outdoor exposure - Megan M. Trusler; Matthew S. Kent; Barry H. Lomax; Christopher H. Vane; Sarah Cook (PLoS ONE, 2025)
A set of unused virgin polystyrene coffee cup lids were distributed in the environment (Sutton Bonington, UK) for a period of 24 months to compare monthly degradation rates across four treatments with variable degrees of exposure to natural UV irradiance (full or reduced exposure) and soil (surface or buried). Analysis of monthly samples (hole-punched discs) from three lids of each treatment via FTIR-ATR indicated that the lids in each treatment displayed varying levels of degradation, ranked as follows: exposure on the ground surface, no shading > exposure on the ground surface, shading> both buried treatments. Principal component analyses (PCAs) and the carbonyl index indicated that photooxidation via sunlight exposure was the primary degradation mechanism for polystyrene under these environmentally relevant conditions. Monthly variations in spectra for each treatment (particularly surface treatments) also indicated that degradation rate was not a continuous process, with a multiple regression establishing correlation between monthly carbonyl index for the first 12 months of the experiment, and both UV irradiance and temperature (p = 0.058). This demonstrated that environmental polystyrene degradation rate was closely related to seasonal cycles in the temperate environment.